Thrombocytopenia and Absent Radii (TAR) Syndrome in Non Identical Twins - Kage, Anup; Marinova, Jasmina (Journal of Nepal Paediatric Society, 2013)
This is a case report of female non identical twins with bilateral absent radii and severe thrombocytopenia. Genetic studies confirmed 1q21.1 deletion. A review of literature showed TAR syndrome in 2 pairs of identical twins (reported in 1986) and one pair of non identical twins (reported in 1979). DOI: http://dx.doi.org/10.3126/jnps.v33i2.8378 J Nepal Paediatr Soc. 2013; 33(2):150-151